FRI0034 Adalimumab reduces CXCR4 expression during inflammatory arthritis and in fibroblast-like synoviocytes and osteoclasts under chronic TNF exposure. (15th June 2017) - Harvey, BP; Li, L; Konrad, M; Knight, H; Westmoreland, S; Ruzek, M; Kaymakcalan, Z
Abstract : Background: The CXCL12/CXCR4 chemokine axis has been implicated in the pathogenesis of RA. The expression of this chemokine and receptor has been shown to be increased in RA synovium, and moreover, CXCR4 levels in synovium have been correlated with joint destruction in RA patients. Objectives: Given that high levels of CXCR4 are associated with RA pathogenesis, we sought to determine whether CXCR4 levels are altered by adalimumab (ADA) both in vivo in RA patients and in the human TNF transgenic mouse model (huTNF Tg197) of arthritis, as well as in vitro with RA fibroblast-like synoviocytes (RA-FLS) and human osteoclast precursors (OCP) following TNF exposure. In addition, we investigated the role of CXCR4 in human osteoclastogenesis (OCgenesis) under chronic TNF exposure. Methods: Public DNA microarray data of synovial tissue from ADA treated RA patients was analyzed for changes in the expression level of various chemokines and their cognate receptors. PBMC populations from ADA treated RA patients taken at baseline, wks. 4 & 12 were assessed by CyTOF for CXCR4. IHC staining was performed on formalin paw sections from wk. 13 placebo control and ADA treated (1 mg/kg i.p.) huTNF Tg197 mice to evaluate CXCR4 expression in various pannus-associated cells. To assess the role of TNF and concomitant ADA treatment on human cultures in vitro, CXCR4 RNA expression was evaluated in RA-FLS treated with conditioned media from PBMCs +/-ADA for 6 hrs., and CXCR4 protein on OCP by flow cytometry in response to 72 hr. M-CSF+RANKL+/-TNF+/-ADA. To demonstrate the role of CXCR4 in OCgenesis, OCP were cultured for 6 d. in M-CSF+RANKL+/-TNF following 30 min. pretreatment with CXCR4 neutralizing antibody. OC maturation and activity were assessed by measuring TRAcP 5b activity and CTX-I release, respectively. Results: Preliminary microarray data analysis of RA synovial tissue demonstrated that active RA patients over-expressed CXCR4 while CXCR4 was significantly normalized (two-fold reduction) in the responders to ADA therapy. In addition, CyTOF analysis of PBMC from ADA treated RA patients indicated a significant 2-fold reduction from baseline in CXCR4 expression on B cells with a modest trend of reduction on CD4+ T cells by wk. 4. In huTNF Tg197 mice, CXCR4 expression in the inflamed pannus (most notably in FLS, lymphocytes and OC) was also decreased by ADA therapy. In vitro human cultures of similar cell types including RA-FLS and OCP were subjected to conditioned media or TNF, respectively, and found to express higher levels of CXCR4 that was reduced with concomitant ADA treatment. Finally, antibody-mediated blockade of CXCR4 on human OCP decreased both TNF-enhanced OC maturation and activity. Conclusions: Our findings demonstrate that ADA therapy reduces CXCR4 expression in vivo both in RA patient PBMCs and in the pannus of huTNF Tg mice with inflammatory arthritis especially in lymphocytes, FLS and OC. Similar results were also observed with our in vitro human cultures of equivalent cell types. More importantly, we've shown that inhibition of CXCR4 can reduce TNF-enhanced OCgenesis in vitro, suggesting that CXCR4 may be a contributing factor to TNF-mediated osteolysis in RA. Acknowledgements: Dr. J. Salfeld and J. Min Disclosure of Interest: B. Harvey Shareholder of: AbbVie, Inc., Employee of: AbbVie, Inc., L. Li Shareholder of: AbbVie, Inc., Employee of: AbbVie, Inc., M. Konrad Shareholder of: AbbVie, Inc., Employee of: AbbVie, Inc., H. Knight Shareholder of: AbbVie, Inc., Employee of: AbbVie, Inc., S. Westmoreland Shareholder of: AbbVie, Inc., Employee of: AbbVie, Inc., M. Ruzek Shareholder of: AbbVie, Inc., Employee of: AbbVie, Inc., Z. Kaymakcalan Shareholder of: AbbVie, Inc., Employee of: AbbVie, Inc.